2008
DOI: 10.1007/s10661-008-0558-1
|View full text |Cite
|
Sign up to set email alerts
|

Urban activity and mercury contamination in estuarine and marine sediments (Southern Brazil)

Abstract: The distribution of mercury in sediments of the Patos Lagoon estuary and nearby coastal marine deposits has been investigated for the period 1998-2008. Polluted urban soils and coastal reclamation fills are the principal sources of high mercury concentrations for shallow estuarine sediments. The shallow sediments that form near the urban area enter the navigation canal and are transported into the ocean. The mercury concentration in sediments of the navigation canal has considerably increased since 2004, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In fact, the different metals were associated with specific sources such as agricultural (Cu), industrial (Cr), and urban (Al, Cu) sources (Klumpp et al 2002). High urbanization has also been related to pollution by Hg in coastal environments (Ferraro et al 2006(Ferraro et al , 2009Mirlean et al 2009) and could be related to high values around the CRE as well. Therefore, there is a combination of several different pollution sources in the hydrographic basin of the Cachoeira River: an industrial hub including paint and dye factories, many agricultural fields with extensive use of pesticides and fertilizers, and untreated and diffuse discharge of urban sewage (Manzini et al 2010).…”
Section: Trace Elements In the Sedimentmentioning
confidence: 99%
“…In fact, the different metals were associated with specific sources such as agricultural (Cu), industrial (Cr), and urban (Al, Cu) sources (Klumpp et al 2002). High urbanization has also been related to pollution by Hg in coastal environments (Ferraro et al 2006(Ferraro et al , 2009Mirlean et al 2009) and could be related to high values around the CRE as well. Therefore, there is a combination of several different pollution sources in the hydrographic basin of the Cachoeira River: an industrial hub including paint and dye factories, many agricultural fields with extensive use of pesticides and fertilizers, and untreated and diffuse discharge of urban sewage (Manzini et al 2010).…”
Section: Trace Elements In the Sedimentmentioning
confidence: 99%
“…Oxy-hydroxides and, secondarily, sulphides and organic matter are the most important metal carriers in sediments of the Patos Lagoon estuary. On the other hand, Mirlean et al (2003bMirlean et al ( , 2009 applied partial extractions for sediment samples and showed that As usually takes its labile form, while Hg does not. Metal speciation and bioavailability of particulate sediment matter were assessed in urban and industrial effluents from the Patos Lagoon estuary.…”
Section: Speciation Of Trace Metals In the Sedimentmentioning
confidence: 99%
“…Polluted urban soils and coastal reclamation fills were confirmed as the main sources of high mercury concentrations in shallow estuarine sediments which enter the navigation channel close to the urban area and are transported into the ocean. Hg concentration in sediments in the navigation channel has considerably increased since 2004 due to the intense reconstruction activity in the urban area (Mirlean et al, 2009). Periodic dredging of the channel strengthens the preconditions for coastal marine sediment contamination by mercury.…”
Section: N P R E S Smentioning
confidence: 99%
See 1 more Smart Citation
“…Pacyna and Pacyna [5] provide estimates of global total anthropogenic mercury emissions over the period 990 to 2000 by United State. Mercury contamination has been found in marine sediments of Southern Brazil for the periods of 1998 to 2008 [6]. Some fishes collected from the same areas also contaminated with mercury ranging from 12.4 ng/g to 216 ng/g [7].…”
Section: Introductionmentioning
confidence: 99%